2009
DOI: 10.1007/s10895-009-0527-2
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Solvation Studies of 1, 5 Diamino Anthraquinone in Binary Liquid Mixtures

Abstract: The absorption and fluorescence spectra of 1,5-diaminoanthraquinone(1,5-DAAQ) have been investigated in organic solvents-Benzene(BZ), Ethanol (ETOH), Acetonitrile (AN), Dimethylformamide (DMF) and Dimethyl sulfoxide (DMSO). There is an intra molecular hydrogen bond formed between quinoid oxygen and the substituents NH(2) [C = O...H-N]. The interaction of the hydrogen atom of - NH(2) leads to red shift in both absorption and fluorescence spectra. The dipole moment ratio of 1,5 DAAQ in ground and excited states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Specifically, ADA was synthesized via amide coupling of 1,5‐diaminoanthraquinone and acyl chloride of 10,12‐pentacosadiynoic acid (PCDA). ADA is soluble in various solvents, and its color (i.e., absorbance in the visible spectral range) and fluorescence excitation/emission properties in solution state were dependent upon solvent polarity (Figure S1, Supporting Information), accounting for the solvatochromism of the anthraquinone moiety [ 39,40 ]…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, ADA was synthesized via amide coupling of 1,5‐diaminoanthraquinone and acyl chloride of 10,12‐pentacosadiynoic acid (PCDA). ADA is soluble in various solvents, and its color (i.e., absorbance in the visible spectral range) and fluorescence excitation/emission properties in solution state were dependent upon solvent polarity (Figure S1, Supporting Information), accounting for the solvatochromism of the anthraquinone moiety [ 39,40 ]…”
Section: Resultsmentioning
confidence: 99%
“…Also 0.25emf2normalf1>1 for both absorption and emission maxima. These observations, both in the zero point energy state (ZPS) and the excited energy state 3OCE, demonstrated that the solute was preferentially solvated by the more polar solvent AN . To understand preferential solvation with nonspecific interactions in the solvent mixture through dielectric enrichment, Suppan's theory of dielectric enrichment for a single shell approximation was applied.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that in both the ground and excited states, 2,5‐DEAPMC dye molecules are preferentially solvated by solvent 1 (DIO) rather than solvent 2 (ACN). This might be due to cluster formation in solvent 2 (ACN) and more monomeric species in solvent 1 (DIO) .…”
Section: Resultsmentioning
confidence: 99%